Genotypic distribution and a potential diagnostic assay of multidrug-resistant tuberculosis in northern thailand - Usanee Anukool (2020)
© 2020 Anukool et al. Introduction: Knowledge of the prevalence and distribution of multidrug-resistant tuberculosis (MDR-TB) genotypes in northern Thailand is still limited. An accurate, rapid, and cost-effective diagnostic of MDR-TB is crucial to improve treatment and control of increased MDR-TB. Materials and Methods: The molecular diagnostic assays named “RIF-RD” and “INH-RD” were designed to detect rifampicin (RIF) and isoniazid (INH) resistance based on real-time PCR and high-resolution melting curve analysis. Applying the ∆Tm cutoff values, the RIF-RD and INH-RD were evaluated against the standard drug susceptibility testing (DST) using 107 and 103 clinical Mycobacterium tuberculosis (Mtb) isolates from northern Thailand. DNA sequence analysis of partial rpoB, katG, and inhA promoter of 73 Mtb isolates, which included 30 MDR-TB, was performed to elucidate the mutations involved with RIF and INH resistance. Results: When compared with the phenotypic DST, RIF-RD targeting rpoB showed sensi-tivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 83.9, 98.6, 96.9, and 92.0%, respectively. The multiplex reaction of the INH-RD targeted both katG and inhA promoter showed high sensitivity, specificity, PPV, and NPV of 97.1, 94.2, 89.2, and 98.5%, respectively. Six patterns of rpoB mutation, predominately at codons 531 (50%) and 526 (40%) along with a rare S522L (3.33%) and D516V (3.33%), were detected. A single pattern of katG mutation (S315T) (63.3%) and four patterns of inhA promoter mutation, predominately −15 (C>T), were found. Approximately, 17% of MDR-TB strains possessed double mutations within the katG and inhA promoter. Conclusion: Up to 86.7% and 96.7% of MDR-TB could be accurately detected by RIF-RD and INH-RD, emphasizing its usefulness as a low unit price assay for rapid screening of MDR-TB, with confirmation of INH resistance in low and middle-income countries. The MDR-TB genotypes provided will be beneficial for TB control and the development of drug-resistant TB diagnostic technology in the future.